Electrospun silk nanofiber loaded with Ag-doped TiO2 with high-reactive facet as multifunctional air filter - Wanwong, Sompit; Sangkhun, Weradesh; Jiamboonsri, Pimsumon; Butburee, Teera (My University, 2023)
Particulate matter (PM) and volatile organic compounds (VOCs) are air pollution that can cause high risk to public health. To protect individuals from air pollution exposure, fibrous filters have been widely employed. In this work, we develop silk nanofibers, which are loaded with Ag-doped TiO2 nanoparticles with exposed (001) (assigned as Ag-TiO2-silk), via electrospinning method and utilized them as multifunctional air filters that can efficiently reduce PM2.5, organic pollutants and microbials. The results showed that Ag-TiO2-silk with a loading of 1 wt% (1%Ag-TiO2-silk) exhibited the best performance among various different Ag-doped samples, as it performed the best as an air filter, which had the highest PM2.5 removal efficiency of 99.04 ± 1.70% with low pressure drop of 34.3 Pa, and also exhibited the highest photodegradation efficiency of formaldehyde. In addition, the Ag-TiO2-silk demonstrated antibacterial activity. These properties make silk composite nanofibers attractive for multifunctional and environmentally-friendly air filter application.